A discourse analysis of Medieval European recipes - Chin, Gillian Sze Min (2019)
Studies concerning the topic of food have found a strong correlation between our eating habits and social and cultural factors. However, recipe language remains to be a relatively unexplored domain and past research have mostly yielded qualitative data. This thesis attempts to explore how recipes can be used as “pseudo-social documents” to understand how language was used in the day-to-day life of Medieval European societies. A total of 15 recipes was collected from three cookbooks dating back to the Late Middle Ages and were analysed using Labov and Waletzky’s narrative analysis framework. It was found that while there are certain universal syntactic features such as imperatives that occur consistently in all recipes, other features like the use of evaluation terms are largely dependent on the purpose of the cookbook and audience’s prior culinary experience and knowledge. In spite of limitations due to the lack of fluency in the original language of two of the cookbooks as well as a limited data set, this thesis lays the foundation for future work on the recipe text form and other food related documents throughout history by introducing new social perspectives in an effort to uncover original insight in the field of historical linguistics.